Spesies Tumbuhan Penyusun Vegetasi Lantai di Wilayah Restorasi Taman Nasional Gunung Merapi di Ngablak, Magelang, Jawa Tengah - Purnomo Purnomo; Retno Peni Sancayaningsih; Dian Wulansari (Universitas Gadjah Mada, 2016)
Vegetation restoration by Mount Merapi National Park (TNGM) in Ngablak, Magelang, Central Java need the floristic data composition of understory vegetation. The objectives of this research were to identify and to determine the importance values of each plants species that composed of that restoration area. Sample collections were conducted using survey method for their morphological characters as voucher specimens that were used for species identification. Vegetation analysis was conducted using the quadratic method; shrubs (5x5 m2), grasses and herbs (1x1 m2), and importance values were analysed using relative frequencies and densities. The result shows that understory vegetation on the restoration area in Ngablak was composed of 60 seed plant species from 18 plant families. There were 7 plant families that dominate the region; Papilionaceae (13 species), Asteraceae (11), Poaceae (Grasses) (10), Cyperaceae (Sedges) (5), Amaranthaceae (3), Mimosaceae (3) and Commelinaceae (3). Plants species that have important value more than 25% in this restoration area were Cymbopogon citratus (sereh), Mimosa pudica (Putri malu), Gomphrena serrata (Bunga kancing), Pannisetum purpureum (Rumput gajah), Ageratum conyzoides (Wedusan), dan Euphatorium inulifolium (kirinyuh). The external factors that influence the growth of the understory vegetation are pH of soil and soil moisture.